Understanding the classical Malay literary framework: A reappraisal of the poetic theories of Vladimir Braginsky and Muhammad Haji Salleh - Ahmad H.Osman, Rahmah (IIUM Press, 2016)
The objective of this article is to understand the classical Malay literary framework through the analysis of different Malay literary texts. The study is based on an analysis of the works of Vladimir Braginsky and Muhammad Haji Salleh, along with the interpretation of selected classical Malay texts. The article seeks to highlight the critical systems in classical Malay literature and in Puitika Sastera Melayu. The study shows that in Braginsky’s work, the author identifies the significance of studying classical Malay literature for understanding its central notion of beauty and “the beautiful” (indah) in Malay literary writings, as well as the concept of “self-awareness” and the concern of Malay writers for “the spiritual benefit” that is embedded in their writings. But in the works of Muhammad Haji Salleh, on the other hand, the author argues that the Malay literary theory, Puitika Sastera Melayu, was preconditioned by the inner structure of the society, which was embedded in the Malay language, milieu and philosophy.